Important Role of Platelets in Modulating Endotoxin-Induced Lung Inflammation in CFTR-Deficient Mice - Zhao, Caiqi (Public Library of Science, 2013)
Mutation of CFTR (cystic fibrosis transmembrane conductance regulator) leads to cystic fibrosis (CF). Patients with CF develop abnormalities of blood platelets and recurrent lung inflammation. However, whether CFTR-mutated platelets play a role in the development of lung inflammation is elusive. Therefore, we intratracheally challenged wildtype and F508del (a common type of CFTR mutation) mice with LPS to observe changes of F508del platelets in the peripheral blood and indexes of lung inflammation (BAL neutrophils and protein levels). Furthermore, we investigated whether or not and how F508del platelets modulate the LPS-induced acute lung inflammation by targeting anti-platelet aggregation, depletion of neutrophils, reconstitution of bone marrow or neutrophils, blockade of P-selectin glycoprotein ligand-1 (PSGL-1), platelet activating factor (PAF), and correction of mutated CFTR trafficking. We found that LPS-challenged F508del mice developed severe thrombocytopenia and had higher levels of plasma TXB2 coincided with neutrophilic lung inflammation relative to wildtype control. Inhibition of F508del platelet aggregation or depletion of F508del neutrophils diminished the LPS-induced lung inflammation in the F508del mice. Moreover, wildtype mice reconstituted with either F508del bone marrow or neutrophils developed worse thrombocytopenia. Blocking PSGL-1, platelet activating factor (PAF), or rectifying trafficking of mutated CFTR in F508del mice diminished and alveolar neutrophil transmigration in the LPS-challenged F508del mice. These findings suggest that F508del platelets and their interaction with neutrophils are requisite for the development of LPS-induced lung inflammation and injury. As such, targeting platelets might be an emerging strategy for dampening recurrent lung inflammation in cystic fibrosis patients.